Reconstruction self-Estem through Al-Ghazali’s concepts among students of Ma’had Al-Jami’ah - Zahratun Khairiyah; Mawardi (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Self-esteem constitutes a foundational pillar of psychological well-being, yet its formation among mahasantri (university-level Islamic boarding school students) remains underexplored, particularly amid intensifying academic pressures and the identity disruptions wrought by globalization. This study aims to examine how the practice of Al-Ghazali's akhlak (Islamic ethics) shapes self-esteem among mahasantri at Ma'had Al Jamiah IAIN Langsa. Employing a qualitative descriptive phenomenological design, twenty mahasantri aged 18–25 were purposively selected based on their engagement in intensive ethical practice. Data were gathered through the 24-item Rosenberg Self-Esteem Scale and semi-structured interviews to elicit participants' lived experiences. Quantitative analysis revealed a strong positive correlation (r = 0.72) between the internalization of ethical values and psychological resilience. Subsequent thematic analysis identified three core themes underlying self-esteem reconstruction: moral grounding as a buffer against existential uncertainty, communal validation within the boarding school environment as a reinforcer of ethical conduct, and the challenge of maintaining integrity in the face of contemporary cultural trends. These findings demonstrate that the systematic integration of Ihya Ulumuddin teachings within a structured residential educational setting offers a viable, holistic model for character development. This study concludes that Islamic ethical education holds significant potential as a culturally responsive strategy for advancing mental health promotion (SDG 3) and enhancing the quality of Islamic higher education (SDG 4), with implications for curriculum design and student well-being policy in pesantren-based institutions